O-56 "I don't want to make my own decisions": Decision control preferences among diverse older adults, advance care planning, and satisfaction with communication. (1st September 2015) - Chiu, C; Feuz, MA; McMahan, RD; Miao, Y; Sudore, Rebecca L
Abstract : Background: Culturally diverse older adults may prefer varying control over medical decisions. Decision control preferences (DCPs) may profoundly affect decision making and communication. Aim: To determine the DCPs of diverse, older adults and whether DCPs are associated with participant characteristics, advance care planning (ACP), and communication satisfaction. Methods: 146 participants were recruited from clinics and senior centres in San Francisco. We assessed DCPs using the Control Preference Scale: doctor makes all decisions (low), shares with doctor (medium), makes own decisions (high). We assessed associations between DCPs and demographics; prior advance directives; ability to make in-the-moment goals-of-care decisions; prior asked questions, self-efficacy, and readiness; and satisfaction with patient-doctor communication (5-pt Likert) using Chi-square and Kruskal-Wallis analysis of variance. Results: Mean age was 71 ± 10 years, 53% were non-white, 47% completed an advance directive, and 70% made goals-of-care decisions. 18% had low DCPs, 33% medium, and 49% high. Older age was the only characteristic associated with DCPs (low: 75 years ±11, medium: 69 ± 10, high: 70 ± 9, p = 0.003). DCPs were not associated with ACP, in-the-moment decisions, or communication satisfaction. Readiness was the only question-asking behaviour associated (low: 3.8 ± 1.2, medium: 4.1 ± 1.2, high: 4.3 ± 1.2, p = 0.05). Discussion: Nearly 1/5 of diverse, older adults want doctors to make their medical decisions. Low DCPs were associated with older age and lower readiness to ask questions, but not race/ethnicity. Yet, older adults with low DCPs still engaged in ACP, asked questions, and reported communication satisfaction. Conclusion: Regardless of DCPs, clinicians can encourage ACP and questions, but need to assess DCPs to provide the desired amount of decision support.